The effects of smoking on cervical lesions observed by colposcopy - Eiad Mansour (Latakia University Journal -Medical Sciences Series, 2023)
This study aimed to find out the effect of smoking on cervical endoscopic and cytological findings. To achieve the aim of the study، the researcher conducted his study in the Department of Obstetrics and Gynecology at Al-Assad University Hospital in Lattakia during the period between 01/03/2011 and 30/06/2012. The study included 170 patients، who underwent Pap smear and cervical magnoscopy to investigate the effect of smoking on cervical endoscopic and cytological findings. The results were compared between a sample of smokers، 85 patients، and a sample of control، ie non-smokers، 85 patients. The study reached several results: - As we found by comparison between the two groups that there was a difference in the percentage of abnormal endoscopic findings: Where the percentage was in the sample of smokers: (31.76%). While the percentage was in the sample of non-smokers: (18.82%). - It was also found that there was a difference between the two groups in the percentage of abnormal cellular findings: Where the percentage was in the sample of smokers: (27.16%). While this percentage in the sample of non-smokers was: (16.51%). This confirms the role of smoking in increasing cervical endoscopic and cellular abnormalities، with an emphasis on the importance of periodic smear detection and magnified cervical endoscopy.